11 - Household-level Social Capital in Cameroon and Children’s Schooling: A Gender Analysis: https://doi.org/10.4314/ad.v35i4.70224 - Atemnkeng, Johannes Tabi (Africa Development, 2021)
This article examines household-level social capital as a determinant of children’s schooling using a cross-sectional data of the 2001 Cameroon Household Survey. Reduced form demand equations of schooling for the entire sample, male and female children are estimated separately. Results indicate that parent’s education and income strongly influence parental decisions towards a child’s schooling. However, social capital, especially in the female dimension, is more important as both male and female children are equally given the opportunity to attend school and there is no gender bias in children’s schooling outcome when parents participate in groups or associations. We recommend the building of social capital by creating associations and encouraging females to be actively involved in such associative groups.